Adolescent experiences of anti‐obesity drugs. Issue 3 (13th May 2015) - White, B.; Jamieson, L.; Clifford, S.; Shield, J. P. H.; Christie, D.; Smith, F.; Wong, I. C. K.; Viner, R. M.
Summary: Only two anti‐obesity drugs (AODs) are frequently prescribed in paediatric obesity, orlistat and metformin. Meta‐analyses show modest benefit in clinical trials, yet analyses of prescribing databases show high levels of discontinuation in routine clinical practice. Increased understanding of young people's experiences taking AOD could result in improved prescribing and outcomes. Semi‐structured interviews were conducted with young people aged 13–18 years and their parents from three specialist obesity clinics, analysed using a general thematic coding methodology. Theme saturation was achieved after interviews with 15 young people and 14 parents (13 parent–child dyads). Three models were developed. Model 1 explored factors influencing commencement of AOD. Six themes emerged: medication as a way out of obesity, enthusiasm and relief at the prospect of pharmaceutical treatment, last ditch attempt for some but not all, passive acceptance of medication, fear as a motivating factor, and unique treatments needed for unique individuals. Model 2 described the inter‐relationship between dosing and side effects; side effects were a significant experience for many young people, and few adhered to prescribed regimens, independently changing lifestyle and dosage to tolerate medications. Model 3 described the patient‐led decision process regarding drug continuation, influenced primarily by side effects and efficacy. Use of AODs is challenging for many adolescents. Multiple factors were identified that could be targeted to improve concordance and maximize efficacy.